Inovasi Pelayanan Publik: Studi Difusi Inovasi Penggunaan Aplikasi Identitas Kependudukan Digital (IKD) di Kota Pekanbaru - Amalia, Herfina; Hartono, Toni (Research and Development Agency Ministry of Home Affairs, 2024)
Digital population identity innovation is present as a form of digital transformation of population documents, for solutions to problems related to population documents. The IKD application is projected by the government to be around 25% of users within one year, so efforts are needed to disseminate innovation to the community for later adoption. This study aims to reveal the strategy for disseminating digital population identity (IKD) application innovations carried out by the Pekanbaru City Population and Civil Registry Office, as well as to analyze the factors that influence the adoption of IKD application innovations for the Pekanbaru City community. The research method is through observation, interviews, and documentation. The results of this study indicate that the use of the IKD application facilitates access, verification of online-based population data, which is equipped with security features to provide more effective, fast and transparent public services. The process of diffusing the IKD application in Pekanbaru City began in early January 2023 with gradual socialization starting from the Pekanbaru City government, schools, sub-district UPTD, RT/RW and levels of society through the outreach program, where the Disdukcapil directly provided an understanding of the IKD application, and was supported through mass media, such as Instagram, Facebook, YouTube, and websites. The social structures that played a role included the Ministry of Home Affairs, the Pekanbaru City Disdukcapil, Sub-district UPTD, and all levels of society. For one year, the IKD application has been used by 8% or 61,372 users of the total population required to have e-KTP in Pekanbaru City. The implementation of the IKD application is still not in accordance with expectations, this is influenced by the lack of public knowledge of the IKD application, ease of innovation, the use of the application is not yet optimal, the application is considered complicated and often errors, and government regulations. In the future, a strategy is needed to increase public enthusiasm and involvement in using the digital population identity (IKD) application. This study is an evaluation for the government in designing strategies so that the digitalization of digital population identity applications can be realized to support better public services.